Multiple origins of freshwater invasion and parental care reflecting ancient vicariances in the bivalve family Cyrenidae (Mollusca) - Haena Kwak; Yucheol Lee; Aileen Tan Shau Hwai; Jiyeon Kim; Tomoyuki Nakano; Joong-Ki Park (Communications Biology, 2024)
Abstract Habitat transitions in living organisms are key innovations often coupled with species diversification after their successful adaptation to new environment. The Cyrenidae is among the most well-known heterodont bivalve groups that have successfully invaded freshwater systems from brackish water environments and display diverse lineage-specific developmental modes. Phylogenetic and molecular clock-based divergence time analyses using 12 complete mitochondrial genome sequences suggest that Cyrenidae species independently colonized freshwater habitats during three distinct spatial and geological periods: one from the American continents approximately in the Early Jurassic and the two others from Australasian/East Asian continents in the Early/Middle Cretaceous and the Paleogene-Neogene boundary, respectively. This study provides significant insight into the temporal and spatial patterns of multiple freshwater invasions, aligning with ancient vicariance events inferred from different geological timelines of plate tectonics. Additionally, mitogenome phylogeny confirms the earlier hypothesis of the repeated parallel evolution of parental care system within this bivalve group.